Preparation method and application of ionic liquid modified graphene material with high electrothermal performance

By modifying the amine-functional imidazole ionic liquid on graphene material and using freeze-drying method, the problem of insufficient CO2 adsorption capacity of ESA materials under DAC conditions is solved, and its electric heating performance and adsorption capacity are significantly improved.

CN117899825BActive Publication Date: 2024-12-24ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410163154.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2024-12-24
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

Existing electrically swing adsorption (ESA) materials do not adsorb CO2 under DAC conditions, and their electrothermal conversion efficiency and adsorption capacity are insufficient, especially due to the lack of loaded amine groups, their performance at high temperatures.

Method used

By modifying the amine-functionalized imidazole-type ionic liquid onto the graphene material and drying by freeze-drying, the microstructure and electronic properties of the material are retained, thereby improving its electric and thermal performance. Specific steps include thermal reduction treatment, argon plasma treatment, oven drying and freeze-drying, and pentaethylene hexamine-2-methylimidazole or tetraethylene pentaamine-2-methylimidazole as ionic liquid modification agent.

Benefits of technology

It significantly improves the electric heating performance of graphene materials, improves the adsorption capacity and electric heating desorption performance of CO2, shortens the heating time, and improves the peak CO2 concentration and desorption rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117899825B_ABST
    Figure CN117899825B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an ionic liquid modified graphene material with high electrothermal performance, comprising: taking a graphene material and loading it into a corundum tube of a tubular furnace for thermal reduction treatment; loading the thermal reduction product into a plasma vapor deposition tube, and performing argon plasma treatment under vacuum conditions to obtain a carrier; placing the carrier in an oven for drying overnight, taking an imidazole-based ionic liquid and the dried carrier and placing them in a reactor, placing them in a blast oven for heating, then taking out the sample and gently blotting it with a paper towel, placing the product in a refrigerator for freezing, taking it out and placing it in a freeze dryer for vacuum drying to obtain the material. The present invention modifies the graphene material with an imidazole-type ionic liquid having conductivity, dries the material by freeze drying during the preparation process, retains the microstructure of the ionic liquid modified graphene material, and thus improves the electrothermal performance of the graphene material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of carbon dioxide capture, and in particular relates to a preparation method and application of an ionic liquid modified graphene material with high electrothermal performance. Background Art

[0002] Electroswing adsorption (ESA) is an emerging CO2 adsorption technology that regenerates the adsorbent by directly converting electrical energy into thermal energy based on Joule heat. ESA materials mainly refer to carbon-based adsorbents with high electrothermal conversion efficiency, such as graphene, carbon nanotubes and carbon fibers, which hardly adsorb CO2 under DAC conditions. The adsorption capacity of ESA materials depends largely on the loaded amine groups.

[0003] Compared with pure organic amines, amine-functionalized imidazolium ionic liquids not only have the ability of pure organic amines to chemically adsorb CO2, but also have good physical and chemical properties of imidazolium ionic liquids, such as thermal stability and electrical conductivity. Freeze-drying to prepare carbon materials has received increasing attention. This technology is a drying method that freezes the material below the freezing point of water and sublimates solid ice to gas under high vacuum conditions, so that the physical structure and physical and chemical properties of the material remain in the state before freeze-drying. Modifying amine-functionalized imidazolium ionic liquids onto ESA materials and drying them by freeze-drying can retain the microstructure of ionic liquids and graphene and the outer electronic properties of carbon atoms, thereby improving their electronic conductivity. Summary of the invention

[0004] In view of the characteristics of the prior art, the present invention provides a method for preparing an ionic liquid modified graphene material with high electrothermal performance, wherein the ionic liquid modified graphene material with high electrothermal performance is prepared by the following method:

[0005] (1) 10 to 30 mg of graphene material is placed into a corundum tube of a tubular furnace and subjected to thermal reduction treatment to obtain a thermally reduced sample.

[0006] (2) 10 to 30 mg of the sample obtained in step (1) is placed in a plasma vapor deposition tube, and the sample is treated with argon plasma for 30 minutes under vacuum conditions with an absolute pressure of less than 30 kPa to obtain a carrier used subsequently.

[0007] (3) The carrier obtained in step (2) is placed in an oven to dry overnight. 10 to 50 mL of imidazole-based ionic liquid and 10 to 30 mg of the carrier are placed in a reaction kettle and heated in a forced air oven at 60 to 100° C. for 8 to 15 hours. The sample is then taken out and the ionic liquid attached to the surface is gently blotted with a paper towel, and the sample is placed in a refrigerator to freeze for 10 to 18 hours. After taking it out, it is placed in a freeze dryer and vacuum dried for 20 to 30 hours to obtain an ionic liquid-modified graphene material.

[0008] Furthermore, the graphene material in step (1) is graphene fiber, graphene film, or graphene aerogel.

[0009] Furthermore, the thermal reduction treatment method in step (1) is: to remove oxygen in the tube by argon-vacuum cycle operation 2 to 4 times, to increase the temperature to 1200-1600°C at a heating rate of 5-15°C (preferably 10°C) per minute under 10-20 mL / min argon protection, maintain for 2-3 hours, and then cool naturally.

[0010] Furthermore, the argon plasma treatment method in step (2) is: removing oxygen in the tube by argon-vacuum cycle operation 2 to 4 times, raising the temperature to 600 to 900° C. at a heating rate of 5 to 15° C. (preferably 10° C.) per minute under 10 to 20 mL / min argon protection, setting the plasma power to 150 to 250 W (preferably 200 W), and the treatment time is 1 to 180 min.

[0011] Furthermore, the oven drying temperature in step (3) is 60-100°C.

[0012] Furthermore, the imidazolyl ionic liquid in step (3) is pentaethylenehexamine-2-methylimidazole [PEHAH][2-MI] or tetraethylenepentamine-2-methylimidazole [TEPAH][2-MI].

[0013] Furthermore, in step (3), the refrigerator temperature is -85°C to -75°C (most preferably -80°C).

[0014] The present invention also provides an investigation into the electrothermal desorption performance of an ionic liquid-modified graphene material with high electrothermal performance.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention modifies a graphene material with an ionic liquid having conductivity, and during the preparation process, the material is dried by a freeze-drying method, thereby retaining the microstructure of the graphene material modified with the ionic liquid, thereby improving the electrothermal performance of the graphene material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 N1s spectrum analysis of dGA (a) and [PEHAH][2-MI]@GA (b) prepared in the present invention. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further described below in conjunction with embodiments.

[0019] The graphene aerogel used in this embodiment is prepared by the following method:

[0020] Take 8 mg of graphene oxide aqueous dispersion (8 mg / g) and spread it on a plastic petri dish with a diameter of 35 mm, put it in a 60°C oven and dry it for 6 hours to obtain graphene oxide flakes. Soak the graphene oxide flakes in 40 vol% hydrazine hydrate solution at room temperature and foam for 90 minutes. Soak the foamed sample in excess anhydrous ethanol for 3 hours, replacing new anhydrous ethanol each time and repeating three times. Repeat the above steps using n-hexane instead of anhydrous ethanol. Put it in a 60°C oven and dry it overnight to obtain graphene aerogel.

[0021] Example 1

[0022] The ionic liquid [PEHAH][2-MI] used in this example was prepared by the following method:

[0023] (1) PEHA (pentaethylenehexamine) and 2-MI (2-methylimidazole) were mixed in pure water at a molar ratio of 1:1, and the volume ratio of solute to solvent was 1:2.

[0024] (2) The mixed solution was stirred at a constant temperature of 40°C and a speed of 1600 r / min for 24 h.

[0025] (3) The reacted solution was distilled under reduced pressure at 70° C. for at least 6 h to a constant weight to obtain the ionic liquid [PEHAH][2-MI].

[0026] The present invention provides a method for preparing graphene aerogel modified by ionic liquid [PEHAH][2-MI], and the specific steps are as follows:

[0027] (1) 30 mg of graphene aerogel was loaded into a corundum tube of a tubular furnace and subjected to thermal reduction treatment (the oxygen in the tube was removed by argon-vacuum cycle operation 3 times, and the temperature was raised to 1450°C at a rate of 10°C per minute under 15 mL / min argon protection, maintained for 2.5 hours, and then cooled naturally) to prepare rGA.

[0028] (2) 25 mg of the sample obtained in step (1) was taken and placed in a plasma vapor deposition tube, and the sample was treated with argon plasma for 30 min under vacuum conditions with an absolute pressure of less than 30 kPa (the oxygen in the tube was removed by argon-vacuum cycle operation 3 times, and the temperature was raised to 700° C. at a rate of 10° C. per minute under 15 mL / min argon protection, and the plasma power was set to 200 W) to obtain dGA.

[0029] (3) The dGA carrier obtained in step (2) was placed in an oven and dried overnight for 12 hours. 25 mL of ionic liquid [PEHAH][2-MI] and 20 mg of the carrier were placed in a reaction kettle and heated in a 90°C forced air oven for 10 hours. The sample was then taken out and the ionic liquid attached to the surface was gently blotted with a paper towel. The sample was placed in a refrigerator and frozen for 12 hours. After being taken out, it was placed in a freeze dryer and vacuum dried for 24 hours to obtain [PEHAH][2-MI]@GA.

[0030] The N1s spectra of dGA and [PEHAH][2-MI]@GA prepared in this example are as follows: Figure 1 As shown in Figure 2, dGA contains almost no nitrogen, while [PEHAH][2-MI]@GA has a nitrogen content of 17%. -NH-, -N=, -NH2, graphitic nitrogen and -N were observed at 398.31 eV, 398.66 eV, 399.57 eV, 400.06 eV and 405.71 eV, respectively. + The unshared electron pair of the nitrogen atom at position 1 of H-2-MI participates in the cyclic conjugation, and the electron density of the nitrogen atom decreases, so the hydrogen atoms connected to it are easily separated as H + The reaction site combines with the primary amino group of PEHA to form a new type of ionic liquid. -N + H-, and graphitic nitrogen can only be formed by covalent bonding of amino molecules to the point defects on the surface of dGA, thus explaining the synthesis of [PEHAH][2-MI]@GA.

[0031] The [PEHAH][2-MI]@GA prepared in this example was placed in an adsorption device connected to a balloon filled with CO2 to adsorb CO2 for 90 minutes. Its adsorption capacity was 5 mmol / g. A 0.6 A current was applied to the material through a copper wire to investigate its electrothermal desorption performance. A stable heating temperature of 80°C was reached in 10 seconds. Compared with pure thermal desorption of the material at 80°C, the heating rate increased by 100%, the CO2 concentration peak increased by 100%, and the time for the peak to appear was shortened by 50%.

[0032] Example 2

[0033] The present invention provides an ionic liquid [PEHAH][2-MI] modified graphene aerogel for electrothermal desorption performance study under the condition of a current of 0.5A. The stable heating temperature of 60°C can be reached in 13s. Compared with the material subjected to pure thermal desorption at 60°C, the heating rate is increased by 80%, the CO2 concentration peak is increased by 90%, and the time for the peak to appear is shortened by 45%.

[0034] Example 3

[0035] The present invention provides an ionic liquid [PEHAH][2-MI] modified graphene aerogel for electrothermal desorption performance study under the condition of a current of 0.4A. The stable heating temperature of 50°C can be reached in 15s. Compared with the thermal desorption of the material at 50°C, the heating rate is increased by 60%, the CO2 concentration peak is increased by 70%, and the time for the peak to appear is shortened by 50%.

[0036] Example 4

[0037] The ionic liquid [TEPAH][2-MI] used in this example was prepared by the following method:

[0038] (1) TEPA (triethylenetetramine) and 2-MI (2-methylimidazole) were mixed in pure water at a molar ratio of 1:1, and the volume ratio of solute to solvent was 1:2.

[0039] (2) The mixed solution was stirred at a constant temperature of 40°C and a speed of 1600 r / min for 24 h.

[0040] (3) The reaction solution was distilled under reduced pressure at 70° C. for at least 6 h to a constant weight to obtain the ionic liquid [TEPAH][2-MI].

[0041] The present invention provides a method for preparing graphene aerogel modified by ionic liquid [TEPAH][2-MI], and the specific steps are as follows:

[0042] (1) 20 mg of graphene aerogel was loaded into a corundum tube of a tubular furnace and subjected to thermal reduction treatment (the oxygen in the tube was removed by argon-vacuum cycle operation twice, and the temperature was raised to 1500°C at a rate of 8°C per minute under 20 mL / min argon protection, maintained for 2 hours, and then naturally cooled) to prepare rGA.

[0043] (2) 20 mg of the sample obtained in step (1) was taken and placed in a plasma vapor deposition tube, and the sample was treated with argon plasma for 30 min under vacuum conditions with an absolute pressure of less than 30 kPa (the oxygen in the tube was removed by argon-vacuum cycle operation twice, and the temperature was raised to 850° C. at a rate of 12° C. per minute under 20 mL / min argon protection, and the plasma power was set to 200 W) to obtain dGA.

[0044] (3) The carrier obtained in step (2) was placed in an oven to dry overnight. 25 mL of ionic liquid [TEPAH][2-MI] and 20 mg of the carrier were placed in a reaction kettle and heated in a 90°C forced air oven for 10 hours. The sample was then taken out and the ionic liquid attached to the surface was gently blotted with a paper towel. The sample was placed in a refrigerator and frozen for 12 hours. After being taken out, it was placed in a freeze dryer and vacuum dried for 24 hours to obtain [TEPAH][2-MI]@GA.

[0045] The [TEPAH][2-MI]@GA prepared in this example was placed in an adsorption device connected to a balloon filled with CO2 to adsorb CO2 for 90 minutes. Its adsorption capacity was 4.5 mmol / g. A 0.6 A current was applied to the material through a copper wire to investigate its electrothermal desorption performance. The stable heating temperature of 80°C was reached in 11 seconds. Compared with the pure thermal desorption of the material at 60°C, the heating rate increased by 78%, the CO2 concentration peak increased by 82%, and the time for the peak to appear was shortened by 47%.

[0046] Example 5

[0047] The present invention provides an ionic liquid [TEPAH][2-MI] modified graphene aerogel for electrothermal desorption performance study under the condition of a current of 0.5A. The stable heating temperature of 60°C can be reached in 13s. Compared with the material subjected to pure thermal desorption at 60°C, the heating rate is increased by 64%, the CO2 concentration peak is increased by 75%, and the time for the peak to appear is shortened by 45%.

[0048] Example 6

[0049] The present invention provides an ionic liquid [TEPAH][2-MI] modified graphene aerogel for electrothermal desorption performance study under the condition of a current of 0.4A. The stable heating temperature of 50°C can be reached in 15s. Compared with the material subjected to pure thermal desorption at 50°C, the heating rate is increased by 41%, the CO2 concentration peak is increased by 47%, and the time for the peak to appear is shortened by 40%.

[0050] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing an ionic liquid-modified graphene material with high electrothermal performance, characterized in that: The ionic liquid modified graphene material is prepared by the following method: (1) Putting the graphene material into a corundum tube of a tubular furnace and performing thermal reduction treatment to obtain a thermal reduction product; (2) placing the thermal reduction product into a plasma vapor deposition tube, and subjecting the product to argon plasma treatment under vacuum conditions with an absolute gas pressure of less than 30 kPa to obtain a carrier; (3) The carrier obtained in step (2) is placed in an oven for drying overnight for 8 to 16 hours, and the imidazolyl ionic liquid and the dried carrier are placed in a reaction kettle, wherein the imidazolyl ionic liquid is hexaethylenepentamine-2-methylimidazole [PEHAH][2-MI] or tetraethylenepentamine-2-methylimidazole [TEPAH][2-MI], and the carrier is placed in a forced air oven for heating for 8 to 15 hours. After that, the sample is taken out and the ionic liquid attached to the surface is gently blotted with a paper towel, and the product is placed in a refrigerator for freezing for 10 to 18 hours. After taking out, the product is placed in a freeze dryer for vacuum drying for 20 to 30 hours to obtain an ionic liquid modified graphene material with high electrothermal performance.

2. The preparation method according to claim 1, characterized in that In step (1), the graphene material is graphene fiber, graphene film, or graphene aerogel.

3. The preparation method according to claim 1, characterized in that: In step (1), the thermal reduction treatment specifically includes: removing oxygen in the tube by argon-vacuum cycle operation 2 to 4 times, raising the temperature to 1200 to 1600°C at a heating rate of 5 to 15°C per minute under the protection of 10 to 20 mL / min argon, maintaining for 2 to 3 hours, and then cooling naturally.

4. The preparation method according to claim 1, characterized in that: In step (2), the argon plasma treatment specifically includes: removing oxygen in the tube by argon-vacuum cycle operation 2 to 4 times, heating the temperature to 600 to 900°C at a rate of 5 to 15°C per minute under the protection of 10 to 20 mL / min argon, setting the plasma power to 150 to 250 W, and the treatment time to 1 to 180 min.

5. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the blast oven is 60-100°C.

6. The preparation method according to claim 1, characterized in that: In step (3), the freezing temperature is -85°C to -75°C.

7. Application of the ionic liquid modified graphene material with high electrothermal performance prepared by the preparation method according to any one of claims 1 to 6 in carbon dioxide capture.

Citation Information

Patent Citations

  • Preparation method of graphene aerogel electrode material

    CN109824037A

  • Functionalized ionic liquid / organic solvent composite system, and preparation method and application thereof

    CN110339672A